Problems of Rendering Architectural Terms in the Lithuanian translation of K. Frampton’s “Modern Architecture: A Critical History” - Posaškova, Aleksandra; Burkšaitienė, Nijolė (Vertimo studijos, 2021)
The article explores problems of translation of architectural terms from English into Lithuanian by analysing the terms found in K. Frampton’s book Modern Architecture: A Critical History and their translation into Lithuanian in Moderniosios architektūros kilmė ir pagrindai (translated by S. Kozulaitė). In order to identify architectural terms in the original text, a special term identification application was created and used. Thus, 132 English architectural terms were identified and semantic analysis of these terms as well as the analysis of their translation was conducted. It was established that the main problems of translating architectural terms were caused by the difficulty of their identification in the original text, their variation and synonymy in Lithuanian. The research results suggest that translation of some architectural terms from English into Lithuanian may be a challenge caused by the difficulty of establishing an equivalent term arising from the existing synonymity or variation of architectural terms in the Lithuanian language.
Keywords: architectural terms; term translation; term identification; equivalency; term variation; synonymity